(untitled) (Education in the 21st Century, 2025)
Left-handedness is considered a biological and neuropsychological trait, expressed through the dominance of motor functions on the left hand or the left side of the body. Although it is recognized as a variation of the norm and is not regarded as a medical or developmental disorder in itself, a number of studies suggest that left-handed children may face challenges in educational adaptation and socio-psychological integration. These difficulties are particularly pronounced among preschool and primary school children who are placed in learning environments primarily designed for right-handed individuals. The objective of this study was to analyze the specifics of diagnosing left-handedness and the associated adaptation issues, based on the results of sociological surveys. Through the use of diagnostic tools, the study aimed to explore left-handed students’ subjective perceptions of their hand dominance, their attitudes towards this trait, and the reactions of their social environment, including teachers, parents, and peers. The results obtained provide a significant foundation for a deeper scientific understanding of the adaptation challenges faced by left-handed students in educational settings. Moreover, they offer insight into the need to revise educational policies and pedagogical practices in order to develop appropriate approaches. Based on the data, it becomes possible to formulate clear recommendations aimed at enhancing the effectiveness of inclusive education and ensuring equal educational opportunities for left-handed children.